Pengaruh Nilai CN (Curve Number) Terhadap Limpasan Permukaan pada Daerah Aliran Sungai Krueng Jalin Kabupaten Aceh Besar - Syahputra, Ichsan; Irfan, Zu (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The Krueng Jalin River is located in Aceh Besar Regency, with a watershed area (DAS) of ± 345.56 km² up to the flood observation point at the Krueng Jalin Bridge. The rain stations mentioned are BPP Indrapuri, BPP Kota Jantho, BPP Lembah Seulawah, BPP Tangse, BPP Mutiara, BPP Keumala, the SIM Meteorology Station, and the Aceh - Indrapuri Climatology Station. Rainfall data was collected over a 10-year period, from 2015 to 2024. The annual maximum daily rainfall ranged from 122 mm (2019) to 200 mm (2023). Hydrological modeling was performed using the HEC-HMS (Hydrologic Engineering Center's Hydrologic Modeling System) application. River modeling used the HEC-RAS (Hydrologic Engineering Center's River Analysis System) application. Return period rainfall is the expected rainfall height to occur once within a specific period. For this study, the return periods were 2, 5, 10, 20, 25, 50, and 100 years, based on an analysis of historical data and hydrological statistics. The statistical hydrological analysis showed return period rainfall from various distribution methods: Gumbel, Normal, Log Normal, and Log Pearson type III. The 100-year return period rainfall (TR-100) was 280.95 mm. The 100-year return period flood discharge (TR-100) was 844.13 m³/sec with a CN value of 50, 1220.32 m³/sec with a CN value of 60, and 1604.90 m³/sec with a CN value of 70.There was an increase in flood discharge as the CN value increased, starting from 31% (844.13 – 1220.32 m³/sec) and reaching 24% (1220.32 – 1604.90 m³/sec). This indicates that any change in land use will tend to be marked by a large increase in surface runoff if the CN value increases within each watershed.